ESTIMATIVA DO CONSUMO DE ÃGUA POR UMA CULTURA DE CEBOLA PELO MÃ‰TODO DE PENMAN - Klar, A. E.; Garcia, G. J.; Moretti Filho, J. (REVISTA DE AGRICULTURA, 2020)
ESTIMATIVA DO CONSUMO DE ÃGUA POR UMA CULTURA DE CEBOLA PELO MÃ‰TODO DE PENMAN